Filmes mistos de alginato de sódio e cera de abelha: preparação, caracterização e aplicação em embalagens para mel de abelha (apis mellifera l.) - Oliveira, Brenda Nathália Fernandes (Universidade Federal Rural do Semi-Árido, 2021)
Plastic packaging plays a key role in the marketing of food, as it is essential to preserve and maintain the characteristics of products for as long as possible. The most used in the world, so far, are biorecalcitrant and come from petroleum-derived polymers, that is, from non-renewable sources and which end up generating an accumulation of non-degradable solid waste in the environment. Thus, this work aimed to obtain and characterize biodegradable films of sodium alginate and beeswax suitable for the manufacture of packaging for honey from Apis mellifera L. Therefore, this took place in two stages: the first one was obtaining and characterization of mixed films of sodium alginate and beeswax in four compositions (Sodium alginate 2%; Sodium alginate 2% with 5% beeswax; Sodium alginate 2% with 10% beeswax; Alginate of 2% sodium with 15% beeswax). In the second stage, the preparation of the packages that were used to store the honey for 60 days was carried out, with physicochemical analyzes being carried out on the honeys on days 0, 7, 15, 30, 45 and 60 days. The results were submitted to ANOVA and comparison of means by the Tukey test with a significance level of 5% (p < 0.05). As for the characterization of the films: those that contained wax in the composition had lower water vapor permeability/water vapor permeability rate (WVP) compared to the others, more yellowish color and greater opacity. In the evaluated mechanical properties, it was possible to observe that at higher levels of wax there was less tensile strength, in addition to greater elasticity. In the solubility results, it was found that films with 5 and 10% wax significantly reduced the solubility compared to the alginate film alone. Regarding the contact angle, the results did not show any significant difference. At different UR%, wax films absorbed less water. In the physicochemical characteristics of honey, wax packaging kept the honey properties within the recommendations for a longer time. As for the durability of the packages, after 30 days of the experiment, all packages without wax, only sodium alginate, had problems, mainly related to leaks and dissolutions of the packages. The packaging with 10% wax is the most durable of all. Thus, it is concluded that the incorporation of wax in the packaging of sodium alginate, especially at a concentration of 10%, was effective in maintaining the physicochemical characteristics of honey within the recommendations for the time researched, in addition to being the one that presented the lowest percentage of defects during the entire experiment
Keywords: Biopolímeros; Mel de abelha; Polissacarídeos; Cera de abelha; Filme Biodegradável; Biopolymers; Honey; Polysaccharides; Beeswax; Biodegradable Film; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE